Required Elements for Success and Benefits of Participation in Camps of an On-The-Land Program in the Inuvialuit Settlement Region - Ollier, Mary; Giles, Audrey R.; Etter, Meghan; Ruttan, Jimmy; Elanik, Nellie; Goose, Ruth; Ipana, Esther (Études/Inuit/Studies, 2022)
We report on a partnership between the Inuvialuit Regional Corporation (IRC) and the University of Ottawa to determine whether/how on-the-land programming offered culturally safe experiences to meet the self-identified needs of the residents of the Inuvialuit Settlement Region. This study draws upon the experiences of participants in the IRC’s land-based healing program, Project Jewel. We used postcolonial theory supported by a decolonization framework and critical Inuit studies to direct this community-based research methodology. The community advisory committee and the research advisory team co-determined semi-structured interviews, sharing circles, and photovoice as the chosen research methods for this project. Results indicate that land-based healing programs considerably enhanced cultural identity and meaningful connections to social support and Inuvialuit heritage in an “on-the-land” environment. Land-based programs may thus offer an alternative and effective healing opportunity for participants who feel uncomfortable or are not being adequately served by conventional community-based or residential treatment programs. Cet article rend compte d’un partenariat entre la Société régionale inuvialuit et l’Université d’Ottawa déterminant si et comment le programme de guérison sur les terres ancestrales offre une expérience culturellement adéquate pour assurer les besoins identifiés par les résidents de la région des Inuvialuit. L’étude se base sur l’expérience des participants du programme de guérison sur les terres ancestrales Jewel développé par la Société régionale inuvialuit. Nous avons utilisé la théorie postcoloniale soutenue par des études critiques inuit et un cadre conceptuel de décolonisation pour orienter notre méthodologie de recherche communautaire. Le comité consultatif communautaire et l’équipe consultative de recherche ont co-déterminé comme méthode de travail pour ce projet des entretiens semi-dirigés, des cercles de partage et un photovox. Les résultats indiquent que les programmes de ...